Methods of measuring milk yield from Galla goats - Nyakalo, S.; Badamana, M.S.; Wanyoike, M.M. (1991)
There are various methods of measuring milk yield from goats. In the present study 84 lactating Galla goats on a Rhodes grass (Chloris gayana) hay basal diet and supplemented with 500g (as is) of a concentrate diet constituting of poultry litter (0, 15, 30 or 45%) were used to compare milk yield estimates using two methods. Milking method 1 involved hand milking first followed by kid suckling of residual milk while method 2 involved a reversal of this procedure where the kids first suckled to their satisfaction followed by hand milking of residual milk. The total milk yield was estimated as the total of the hand milked and suckled milk; the kids milk intake was estimated by the weigh-suckle-weigh method. The goats were milked weekly on two consecutive days. On the first day the milking method I was used both in the morning and in the evening while method 2 was used on the second day. The total daily milk yield was then estimated as the total milk yield obtained in the morning and in the evening. The total daily milk yield estimates with both milking methods were not significantly (P>0.05) different. However, whatever the milking method used, the amount of milk consumed by the kid was higher than that obtained by hand stripping.